2020
DOI: 10.3920/jaan2020.0015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary inclusion of GuarPro F-71 on the growth performance and nutrient metabolism in young growing pigs

Abstract: Using alternative feedstuffs can be a feasible measure to reduce swine production cost. GuarPro F-71 (GP71), a newly developed guar meal product, is considered as a potential protein source for pigs. This preliminary study was conducted to evaluate the effects of GP71 inclusion in feed on growth performance and nutrient metabolism of growing pigs. Sixty crossbred barrows (31.9±1.84 kg body weight (BW)) were allotted to one of five dietary treatments in a completely randomised experiment design, with four pens/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
4
1
Order By: Relevance
“…Pigs in the group fed diets containing 25% GM protein obtained the best performance, as evidenced by the lowest feed conversion ratio and the highest growth rate. On the other hand, Hasan et al [4] observed a negative impact on ADFI and ADG when using GuarPro F-71 in young pigs' diets as a 75% replacement for SM, which showed a linear decrease as guar inclusion increased but not a decrease in feed efficiency, in conflict with our results and those of Heo et al [46]. GM diets had no noticeable impact on ADFI in growing-finishing pigs [47].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Pigs in the group fed diets containing 25% GM protein obtained the best performance, as evidenced by the lowest feed conversion ratio and the highest growth rate. On the other hand, Hasan et al [4] observed a negative impact on ADFI and ADG when using GuarPro F-71 in young pigs' diets as a 75% replacement for SM, which showed a linear decrease as guar inclusion increased but not a decrease in feed efficiency, in conflict with our results and those of Heo et al [46]. GM diets had no noticeable impact on ADFI in growing-finishing pigs [47].…”
Section: Discussioncontrasting
confidence: 99%
“…In previous research, dietary guar meal was not sufficiently studied as an alternative to traditional soybean meal [4]. Previous studies attempted to identify the ideal levels of dietary GM that could be used without adversely impacting performance [40], and few studies have investigated the impact of guar inclusion on carcass characteristics [41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, high levels of guar meal can depress feed efficiency and animal growth due to the presence of antinutritional factors and poor palatability (Gutierrez et al, 2007). The effects of guar by-products on pig performance remain insufficiently investigated (Heo et al, 2009;Hasan et al, 2020). The inclusion of new ingredients in animal diets may affect the health and performance of animals.…”
mentioning
confidence: 99%